Multi-Factor Analysis of Single-Center Asthma Control in Xiamen, China - Zhu, Yu; Zhong, Taoling; Ge, Dandan; Li, Qiyuan; Wu, Jinzhun (Frontiers in Pediatrics, 2019)
We evaluated the effects of air pollutants, age, allergic history, family allergic history, treatment, treatment steps and compliance on uncontrolled childhood asthma in Xiamen, China. The clinical data of children with asthma in the pediatric outpatient department of the First Affiliated Hospital of Xiamen University from January 2016 to June 2018 were analyzed retrospectively. According to the assessment of the patients’ outcome including well-controlled, partly-controlled and uncontrolled, 7,211 cases of 3,268 patients were selected. Rank sum test and ordered multi-class logistic regression analysis were used. In the rank sum test, age, allergic history, family allergic history, season, treatment, treatment steps and compliance were found associated with uncontrolled rate (all P < 0.001). Logistic regression analysis showed that PM10, NO2, and SO2 raised uncontrolled-asthma rate (aOR 1.311, aOR 1.281, aOR 1.252, respectively). Older children had lower uncontrolled rate (OR=0.849, 95% CI: 0.758-0.950), children with higher treatment steps had higher uncontrolled rate (OR=1.227, 95%CI: 1.040-1.448), and children with better treatment compliance have lower uncontrolled rate (OR = 0.374 95% CI: 0.331-0.424). The order of the uncontrolled rate of asthma from high to low was winter, spring, autumn and summer. PM10, NO2, SO2, age, season, treatment steps and treatment compliance have significance for predicting the control rate of childhood asthma in Xiamen, China.